Die Bauten des Amasis im Vorfeld des Satet-Tempels von Elephantine: Teil I. Die Inschriften - Seidlmayer, Stephan Johannes (Mitteilungen des Deutschen Archäologischen Instituts Kairo, 2024)
In the later part of the Saite Dynasty, royal building activity in the area of the First Cataract was resumed on an ambitious scale. In this context, King Amasis erected two monumental constructions in front of the temple of Satet on Elephantine, namely an entrance colonnade and a monumental gate. Both of these buildings could be reconstructed mainly from blocks recovered from the foundations of the Ptolemaic temple of Satet by Werner Kaiser. A renewed study of this material revealed a host of additional information. In the present contribution, the remaining inscriptions of both buildings are presented and discussed. As an important fact, it could be noted that the names and titles of King Amasis were erased on most of his monuments in the cataract area, as was noted before on his monuments from sites in the Delta. [...]